Giant multiple caloric effects in charge transition ferrimagnet - Yoshihisa Kosugi (Nature Portfolio, 2021)
Abstract Caloric effects of solids can provide us with innovative refrigeration systems more efficient and environment-friendly than the widely-used conventional vapor-compression cooling systems. Exploring novel caloric materials is challenging but critically important in developing future technologies. Here we discovered that the quadruple perovskite structure ferrimagnet BiCu3Cr4O12 shows large multiple caloric effects at the first-order charge transition occurring around 190 K. Large latent heat and the corresponding isothermal entropy change, 28.2 J K−1 kg−1, can be utilized by applying both magnetic fields (a magnetocaloric effect) and pressure (a barocaloric effect). Adiabatic temperature changes reach 3.9 K for the 50 kOe magnetic field and 4.8 K for the 4.9 kbar pressure, and thus highly efficient thermal controls are achieved in multiple ways.